Appropriateness of Antiplatelet Therapy and Proton Pump Inhibitor Prescribing in End-Stage Kidney Disease: A Retrospective Quality Investigation Study - Michael Che; Sumaiya Ahmed; Ryan Chan; Ayub Akbari; Deborah Zimmerman (Canadian Journal of Kidney Health and Disease)
Background: Patients with end-stage kidney disease (ESKD) have high rates of gastrointestinal bleeding due to several risk factors including platelet dysfunction, comorbid illness, and use of antiplatelet medications. Proton pump inhibitors (PPIs) reduce gastrointestinal bleeding and are recommended for high-risk patients such as those prescribed dual antiplatelet therapy (DAPT). Whether inappropriate duration of DAPT therapy and/or lack of appropriate PPI use contribute to the known elevated risk of gastrointestinal bleeding in hemodialysis patients is not known. Objectives: To determine whether patients with ESKD are appropriately prescribed DAPT and PPI therapy. Design: Retrospective cross-sectional, quality investigation. Setting: Satellite hemodialysis unit of a tertiary care center in Ontario, Canada. Patients: All patients with ESKD treated at a satellite hemodialysis unit of a tertiary care hospital. Measurements: Number of patients prescribed antiplatelets, PPIs, anticoagulants, non-steroidal anti-inflammatory drugs (NSAIDs), and corticosteroids; indications for aforementioned medications. Methods: A chart review was performed to elucidate patients’ medical history and pertinent medications. Patients’ indications for PPI and DAPT were extracted from their electronic medical records. Results: Out of 88 patients with ESKD treated with hemodialysis, 44 were on antiplatelet therapy (4 on DAPT), 1 on NSAID, 12 on corticosteroids, 7 on oral anticoagulants, 2 on histamine H2-receptor antagonists, and 39 on PPIs. Fourteen percent of PPI users had absolute indication for therapy. One patient in whom PPI therapy was indicated was not prescribed one. Out of 4 patients on DAPT, 3 had current indications for DAPT, whereas 1 had a prior indication. Limitations: Single-center study; medication lists obtained from electronic medical records not confirmed by patient interview. Conclusions: At the time of this study, 3% of patients with ESKD treated with hemodialysis had a current indication for DAPT. One patient prescribed DAPT no longer met indication for therapy and was reduced to single antiplatelet therapy. Only one patient with an absolute indication for PPI therapy had not been prescribed one. Overall, it appears that prescribing patterns of DAPT and PPI at our center are unlikely to be a major contributor to the known increased risk of gastrointestinal bleeding in patients treated with hemodialysis. However, this may not be true of all units; ensuring regular medication reviews are undertaken may enhance appropriate prescribing.